An analysis of educational programs of public workers’ unions: the case of Kamu Emekçileri Sendikaları Konfederasyonu (The Confederation of Public Workers' Unions) - Öztürk, Şengül. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2014., 2014)
This research was conducted in order to analyze the attitude of public workers’ unions towards union education and the education programs organized by these unions. The sample of this research consists of the headquarters of eleven unions organized under the Confederation of Public Workers’ Unions (KESK). Due to the research questions, eight main dimensions of union education were analyzed. These dimensions consist of the purposes of union education and the problems faced, the kinds and contents of the educations, the selection procedure of the participants, union education programs for women and women’s participation to these programs, the motivation of union members, teaching methods and materials, educational staff and the evaluation processes of these educations.
Keywords: Labor union members -- Education (Continuing education).